Baseline anthropometric measurements and Obesity among students in Sagamu, Ogun State, southwest, Nigeria - Emmanuel Taiwo; Lateef olatunji O Thanni (Babcock University Medical Journal, 2022)
Objectives: This study was designed to determine the anthropometric characteristics and prevalence of obesity among secondary and undergraduate students in Sagamu.